An investigation of harmonic impacts from ASD under sinusoidal supply voltage - Tan Kheng Hui (School of Electrical System Engineering, University Malaysia Perlis, 2011)
This project basically is investigates the effect of type of supply voltage to ASD three phase and single phase. The type of voltage sources are step, ramp, repeating sequence and sine wave. A complete analytical model is developed to calculate the time domain waveform and the harmonic components of the ASD, and design filter to improve the power factor and reduce harmonic. The harmonic is the major source of sine waveform distortion. The increased use the nonlinear for equipment have caused harmonics to become more common and the harmonic currents is usually caused by nonlinear loads, like adjustable speed drives. Nonlinear loads cause harmonic currents to change from a sinusoidal current to a non-sinusoidal current by drawing short bursts of current each cycle or interrupting the current during a cycle. In harmonics, Total Harmonic Distortion (THD) is a way to evaluate the voltage distortion effects of injecting harmonic currents into the utilitys system. THD is also is used to characterize distortion in both current and voltage waves and power factor is a way to measure the amount of reactive power required to supply an electrical system and an end-users facility, also is measuring the phase difference between voltage and current.